Achados da tomografia computadorizada de alta resolução em pacientes pediátricos com asma grave - Silva, Thiago Krieger Bento da (2018)
Introduction: Quantitative computed tomography (CT) findings in adults with asthma have been correlated with clinical features and pulmonary function tests and used as biomarkers to predict disease severity. However, this correlation is still unclear in children with severe asthma. Purpose: To compare chest CT quantitative parameters in children with severe asthma and healthy individuals, correlating with data from pulmonary function tests, laboratory findings, and hospitalizations due to asthma. Methods: We retrospectively analyzed CT data from 19 school-aged children (5-17 years) with severe asthma and 19 control school-aged children with pectus excavatum. The following CT parameters were evaluated: total lung volume (TLV), mean lung density (MLD), CT air trapping index (AT%) (attenuation < –856 HU), airway wall thickness (AWT), and percentage of airway wall thickness (AWT%). MDCT data were correlated to the following clinical parameters: forced expiratory volume in 1 second (FEV1), forced vital capacity (FVC), forced expiratory flow at 25-75% (FEF 25-75%), FEV1/FVC ratio, sputum and bronchoalveolar lavage analysis, serum IgE levels, and previous hospitalizations due to asthma. Results: asthma patients presented higher mean values of AT% (23.8±6.7% vs. controls, 9.7±3.2%), AWT (1.46±0.22mm vs. controls, 0.47±0.15mm), and AWT% (74.1±3.9% vs. controls, 51.7±6.1%), and a lower MLD (-735 ± 28 HU vs. controls, -666±19 HU). Mean AT% was 29.0 ± 4.7% in subjects with previous hospitalization against 19.2 ± 5.0% in those with no prior hospitalization (p<0.001). AT% presented very strong negative correlations with FVC (r=-0.933, p<0.001) and FEV1 (r=-0.841, p<0.001) and a moderate correlation with FEF 25-75% (r=-0.608, p=0.007). AT% correlation with FEV1/FVC ratio and serum IgE was weak (r=-0.184, p=0.452, and r=-0.363, p=0.202). Conclusion: children with severe asthma present differences in quantitative chest CT scans compared to healthy controls with strong correlations with pulmonary function tests and previous hospitalizations due to asthma. Keywords: asthma; children; quantitative computed tomography; pulmonary function tests; biomarkers.